Colonoscopic Splenic Injury: A Simplified Radiologic Approach - Tara Chen; Qiu Tong; Alexander Kurchin (Case Reports in Gastrointestinal Medicine)
Colonoscopy is a commonly performed procedure for diagnosis and treatment of large bowel diseases. Recognized complications include bleeding and perforation. Splenic injury during colonoscopy is a rare complication. We report a case of a 73-year-old woman who presented with left-sided abdominal pain after colonoscopy with finding of splenic injury on CT scan. She was managed conservatively. We discuss the diagnostic and therapeutic approach to colonoscopic splenic injury.